The structure of isotactic polypropylene in composites filled with lignocellulosic material. Issue 4 (19th May 2019) - Paukszta, D.; Szostak, M.; Bednarek, W. H; Maciejczak, E.
ABSTRACT: Biodegradability of fillers, interesting physical and mechanical properties of polypropylene/lignocellulosic materials are essential motives for undertaking studies of various properties of such materials. Up to now, there have been no complex investigations defining processing of polypropylene/rapeseed straw composites. This study presents the results of research into finding optimal technological parameters of extrusion and injection molding methods. The structural investigations were done using the wide-angle X-ray scattering method. Crystallization of polypropylene in composites filled with rapeseed straw is connected with interfacial interactions, such as shearing forces at the boundary of phases: polypropylene matrix—mold wall—lignocellulosic filler. The value of the melt flow index (MFR) for polypropylene influences the crystallization structure of the crystallization in the injection molding process. Moreover, various parts of dumbbells have different structure of the matrix, which is caused by shearing forces and cooling conditions during the polypropylene processing.